Integrating Scrum development process with UX design flow - Nora Khaled Al Ghanmi; Nor Shahida Mohd Jamail (Institute of Advanced Engineering and Science, 2020)
Nowadays, Agile software development practices are being widely adapted all over the world. Scrum is one of the most known Agile models, it satisfies the business needs and put the main focus on the product. One common challenge for the development of customer-facing products is having a good user experience. This paper presents integrating Scrum development process with user experience design flow. In this study, papers relating to the topic of user experience (UX) process integration with Agile development process, how to measure it and how to improve it, from the year 2010 onwards are reviewed. This is to identify how organizations can integrate UX design flow and Scrum development and get the benefits of both. The conducted review identifies a number of limitations in the existing integrations efforts. A proposed process model to resolve these limitations is presented. Along with our experience in implementing it on an ongoing software development project. The results of applying this process, its impact on the project outcomes quality and the employees’ satisfaction with the process are discussed. The goal of this study is to aid organizations in integrating UX design into their development process.